1999
DOI: 10.1046/j.1365-2141.1999.01516.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis for fludarabine therapy of chronic lymphocytic leukaemia based on ex vivo drug response by DiSC assay

Abstract: The cytotoxic antimetabolite fludarabine is a widely used active agent in chronic lymphocytic leukaemia (CLL). However, cost and occasional adverse side‐effects necessitate careful use. Identifying before treatment patients not likely to benefit from fludarabine could advance disease management both clinically and financially. We used the DiSC (differential staining cytotoxicity) assay, an ex vivo apoptotic drug response test, to identify the sensitivity or resistance to fludarabine of lymphocytes from B‐cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 31 publications
(43 reference statements)
2
31
0
Order By: Relevance
“…A model for these pathways of cell death induction by nucleoside analogues is shown in Figure 14. The further elucidation of these signaling events is warranted, especially in view of the impressive clinical activity of these compounds and the deleterious consequences when resistance to nucleoside analogues arises (Bosanquet and Bell, 1996;Bosanquet et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…A model for these pathways of cell death induction by nucleoside analogues is shown in Figure 14. The further elucidation of these signaling events is warranted, especially in view of the impressive clinical activity of these compounds and the deleterious consequences when resistance to nucleoside analogues arises (Bosanquet and Bell, 1996;Bosanquet et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10]23 Patients treated with assay-sensitive drugs are eight times more likely to respond to treatment than those treated with assay-resistant drugs. 10 In a study of breast cancer patients, it was concluded that clinicians managed patients with a highly treatable disease on the basis of age rather than physiological status, thereby worsening the prognosis for older patients.…”
Section: Figurementioning
confidence: 99%
“…24 CLL is eminently treatable and DiSC assay guided therapy can make economic sense; life could be extended for £1470 per life year gained, 25 and expensive and toxic therapy that is highly unlikely to be effective can be avoided. 8 Although studies have shown a significantly greater prevalence of severe and lethal toxicity in elderly lymphoma patients treated with intensive chemotherapy regimens, 26 age alone should not be the determining factor in modifying treatment in CLL. Cancer treatment in the elderly is remarkably safe when the co-morbid conditions are also treated.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Although earlier laboratory assays based on drug-induced growth inhibition (e.g. H 3 *-thymidine incorporation, clonogenic) have consistently failed to provide clinically relevant information, newer methods that incorporate cell-death measures as surrogates of drug-induced apoptosis have been shown to correlate with response, time to progression, and survival in human haematologic and solid tumours (Bosanquet et al, 1999;Cortazar and Johnson, 1999;Nagourney et al, 2000Nagourney et al, , 2003. The realisation that most chemotherapeutic agents exert their cytotoxic effects through apoptosis (Reed, 1999) supports the use of cell-death assay in the study of topotecan's antitumour activity in human neoplasms.…”
mentioning
confidence: 99%